Bad Times, Bad Jobs? How Recessions Affect Early Career Trajectories - Parag Mahajan; Dhiren Patki; Heiko Stüber (Institute of Labor Economics (IZA), 2024)
Workers who enter the labor market during recessions experience lasting earnings losses, but the role of non-pay amenities in exacerbating or counteracting these losses remains unknown. Using population-scale data from Germany, we find that labor market entry during recessions generates a 5 percent reduction in earnings cumulated over the first decade of experience. Implementing a revealed-preference estimator of employer quality that aggregates information from the universe of worker moves across employers, we find that 17 percent of recession-induced earnings losses are compensated by non-pay amenities. Purely pecuniary estimates can therefore overstate the welfare costs of labor market entry during recessions.
Keywords: E32; J24; J31; J32; 330; earnings inequality; recessions; non-pay amenities